MARKET INTEGRATION AND PRICE TRANSMISSION OF CAYENNE PEPPER IN INDONESIA - Faisyatul Hilmiyah; Agus Supriono (JSEP (Journal of Social and Agricultural Economics), 2022)
Cayenne pepper is a horticultural commodity that its production to be seasonal so cause the supply of cayenne pepper to be unavailable in sufficient quantities throughout the year and the price to be fluctuative. Based on this, this study aims to 1) analyze price behavior and the level of price fluctuations of cayenne pepper using the coefficient of variation 2) analyze market integration using Johansen Cointegration Test, and 3) analyze price transmission using the VAR (Vector Auto Regression) / VECM (Vector Error Correction Model). The results show that 1) The price of cayenne pepper is high when production decreases (December-February and July-August), and low when production is abundant (March-June and September-November). The price of cayenne pepper at the consumer and producer levels has a high and unstable level of fluctuation with a coefficient of variation (KV) respectively of 23.9% and 19.7%, 2) The trace statistic value (106.41) > critical value (16.36) so that the producer and consumer markets of cayenne pepper in Indonesia have been vertically integrated, 3) Price transmission is imperfect. In the event of a price shock, at the producer and consumer level, price adjustments will be made towards long-term equilibrium respectively of -0.103 and -0.279.